2015
DOI: 10.1097/ncc.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Suffering

Abstract: Nurses need to be sensitive toward the religious faiths of their patients and provide culturally appropriate care for them. Nursing interventions to maintain hope and connectedness should be promoted by respecting the patients' expressions of hope and supporting the involvement of family members in end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
0
19
0
4
Order By: Relevance
“…Findings also revealed that the most common sampling technique resulted in convenience sampling (n = 11) Bentur et al 2014;Blinderman and Cherny 2005;Chio et al 2008;Coward and Kahn 2004;Hajdarevic et al 2014;Halstead and Hull 2001;Perreault and Bourbonnais 2005;Shih et al 2009;, purposive (n = 4) (Chao et al 2002;Farsi 2015;Nilmanat et al 2015;Rahnama et al 2012), snowball (n = 2) (Albaugh 2003;Lindholm et al 2002), theoretical , and intentional .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings also revealed that the most common sampling technique resulted in convenience sampling (n = 11) Bentur et al 2014;Blinderman and Cherny 2005;Chio et al 2008;Coward and Kahn 2004;Hajdarevic et al 2014;Halstead and Hull 2001;Perreault and Bourbonnais 2005;Shih et al 2009;, purposive (n = 4) (Chao et al 2002;Farsi 2015;Nilmanat et al 2015;Rahnama et al 2012), snowball (n = 2) (Albaugh 2003;Lindholm et al 2002), theoretical , and intentional .…”
Section: Resultsmentioning
confidence: 99%
“…The qualitative methods most used were phenomenology (n = 15) (Albaugh 2003;Asgeirsdottir et al 2013;Bentur et al 2014;Chao et al 2002;Chio et al 2008;Coward and Kahn 2004;Hajdarevic et al 2014;Lindholm et al 2002;McGrath 2002;Montoya-Juarez et al 2013;Nilmanat et al 2015;Perreault and Bourbonnais 2005;Shih et al 2009;, grounded theory (n = 3) (Farsi 2015;Halstead and Hull 2001;Kawa et al 2003), case study (n = 3) Loh 2004), descriptive method (n = 1) , and ethnography (n = 1) . About the phenomenology method, most studies used a Hermeneutic approach (n = 4) (Chao et al 2002;Chio et al 2008;Hajdarevic et al 2014;Shih et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enfocar el cuidado al final de la vida en encontrar en sentido en la vida y mejorar su crecimiento espiritual hacia la calidad de vida del grupo familiar. Entregar un cuidado culturalmente adecuado: facilitando rituales, meditación 22 .…”
Section: Emociones Adaptación Tratamiento 14unclassified